Should unemployment insurance be centralized in a state union? Unearthing a principle of efficient federation building - Robert Fenge; Max Friese (The Scandinavian Journal of Economics, 2022)
Our study compares the efficiency of unemployment insurance programs in a state union. A centralized insurance will pool the cost of unemployment; this results in a collective bargaining in the member states, which leads to excessively high wages and inefficient insurance. Those high wages attract workers who reduce the outsourced economic cost of unemployment. Only with perfect mobility, this opposing migration effect completely outweighs the pooling effect, and the insurance is no longer inefficient when centralized. Furthermore, we conclude that a principle of efficient federal systems might be that fiscally linked economic policies and institutions should be governed on the same federative level.
Keywords: 330; Centralization; fiscal federalism; imperfect labor markets; migration; vertical fiscal externality